Developmental dyslexia: A deficit in magnocellular-parvocellular co-activation, not simply in pure magnocellular activation. (June 2019) - Contemori, Giulio; Battaglini, Luca; Barollo, Michele; Ciavarelli, Ambra; Casco, Clara
Abstract: The magnocellular deficit theory of dyslexia suggests a selective impairment in contrast detection of stimuli involving pure magnocellular response (e.g. Gabor patches of 0.5 c/deg, 30 Hz, low contrast). An alternative hypothesis is that, dyslexia may be associated with a reduction of typical facilitation that normal readers present for stimuli relying on low-level magno-parvo co-activation, relative to stimuli eliciting pure magno activation. According to this hypothesis, any advantage in contrast sensitivity, produced by either decreasing stimuli temporal frequency (from 30 to 10 Hz, Experiment 1) or using static stimuli of increasing spatial frequency (from 0.5 to 4 c/deg, Experiment 2), would be ascribed to the coexisting responses of the magnocellular and parvocellular systems. In the control group, this advantage in contrast sensitivity was found for a 0.5 c/deg Gabor (either static or flickering at 10 Hz) and for a static Gabor of 4 c/deg. In contrast to magnocellular deficit theory predictions, dyslexic individuals showed no deficit in the unmixed magnocellular response. However, they showed no advantage when the relative weight between magnocellular and parvocellular inputs was thrown off balance in favor of the latter. These results suggest that in order to interpret low-level visual deficits in dyslexia, it is worth considering that fast, feedforward low-frequency representations of spatial structures may result from the coexisting responses of two systems. Our results suggest that in dyslexia, the relative contribution of these two systems in visual processing is perturbed, and that this may have detrimental consequences in word processing, both within the parafovea and the fovea during fixation.